Duodenal-jejunal bypass liner implantation provokes rapid weight loss and improved glycemic control, accompanied by elevated fasting ghrelin levels - Koehestanie, Parweez; Dogan, Kemal; Berends, Frits; Janssen, Ignace; Wahab, Peter; Groenen, Marcel; Müller, Michael; de Wit, Nicole (Endoscopy International Open, 2014)
Background and study aims: Endoscopic implantation of a duodenal-jejunal bypass liner (DJBL) is a novel bariatric technique to induce weight loss and remission of type 2 diabetes mellitus. Placement of the DJBL mimics the bypass component of the Roux-en-Y gastric bypass (RYGB) procedure. In this observational study, we evaluated improvement of glycemic control and weight loss in the course of the treatment (0 – 24 weeks after DJBL implantation) and analyzed accompanying gut hormone responses.Patients and methods: 12 obese individuals with type 2 diabetes were selected for DJBL implantation. Body weight, fat mass, and fasting plasma levels of glucose, insulin, C-peptide, and glycated hemoglobin (HbA1c), were analyzed at 0, 1, 4 and 24 weeks post-implant. Fasting ghrelin, gastric inhibitory peptide (GIP), and glucagon-like peptide (GLP-1) were determined at 0, 1 and 4 weeks post-implant.Results: Besides significant weight loss, fat mass, fasting insulin, and homeostasis model assessment-estimated insulin resistance (HOMA-IR) index were also significantly decreased after DJBL implantation and a 42 % reduction was found in diabetes medication (P < 0.05). The fasting GLP-1 response in the first 4 weeks post-implant was significantly correlated with the fasting insulin and HOMA-IR response. Fasting ghrelin was found to be significantly elevated, in contrast to the decrease in ghrelin that is found after RYGB surgery.Conclusions: DJBL implantation provoked significant weight loss, a decrease in fat mass, and an early remission of type 2 diabetes, comparable to results seen after RYGB surgery. Gut hormone analyses revealed a potential role of fasting GLP-1 in early remission of type 2 diabetes. Interestingly, the DJBL-induced elevation of ghrelin contradicts the suggested role of reduced ghrelin levels after RYGB in improvement of glycemic control.